Mn Pretreatment Improves the Physiological Resistance and Root Exudation of Celosia argentea Linn. to Cadmium Stress - You, Shaohong; Deng, Zhenliang; Chen, Mouyixing; Zheng, Yingyi; Liu, Jiu; Jiang, Pingping (International journal of environmental research and public health, 2023)
Phytoextraction using Celosia argentea Linn. by Mn pretreatment can potentially decontaminate Cd-contaminated soils. However, the mechanism that accelerates the Cd bioaccumulation is still unknown. In order to study the effect and mechanism of Mn pretreatment on Cd bioaccumulation in C. argentea, the hydroponic experiments were set to determine the chlorophyll content, antioxidant enzyme activity, malondialdehyde content, and root exudation of C. argentea. The results indicated that after seven days of Mn pretreatment, both the biomass and Cd concentrations in plants increased compared to the control group. One of the mechanisms for this was the improvement in the physiological resistance of C. argentea following pretreatment with Mn. Compared with Cd stress alone, Mn pretreatment increased photosynthesis and reduced membrane lipid peroxidation. Meanwhile, the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) were significantly reduced in leaves of C. argentea after Mn pretreatment through the reduction in the production of reactive oxygen species. In addition, Mn promoted the exudation of organic acids in the roots of C. argentea. The contents of citric and malic acids increased by 55.3% and 26.4%, respectively, which may be another important reason for Mn pretreatment increasing Cd bioaccumulation in C. argentea. Therefore, the present work shows that the pretreatment of seedlings with Mn can provide a meaningful strategy to improve the remediation efficiency of Cd-contaminated soils by C. argentea.